Psychology’s Crisis of Place - Malherbe, Nick (PINS-Psychology in Society, 2024)
Dlamini, S. (2024). Beyond the pretty white affair: Training Africa-centring psychologists for the future. Unisa Press. 121 pages. ISBN: 978-1-77615-204-9